THE EROSION OF THE SALDUZ DOCTRINE IN THE CASES OF IBRAHIM AND OTHERS V. THE UNITED KINGDOM AND BEUZE V. BELGIUM - Faruk H. Avdić (Revija za kriminologiju i krivično pravo)
The so-called Salduz doctrine that concerns the right to a fair trial and the right to the defense attorney emerged from the case of Salduz v. Turkey, decided on the part of the European Court of Human Rights where the Grand Chamber found the violation of Article 6, paragraph 3(c) of the Convention for the Protection of Human Rights and Fundamental Freedoms. In this connection, the aim of this paper is twofold. In the first place, the paper aims to demonstrate how the European Court of Human Rights has overturned the two main tenents of the so-called Salduz doctrine derived from its landmark case of Salduz v. Turkey in its later Judgments delivered in the case of Ibrahim and Others v. the United Kingdom and the case of Beuze v. Belgium. The two tenets derived from the Salduz doctrine being examined in the paper are the right to access to the defense attorney as a rule during pre-trial proceedings and the absolute exclusionary rule. In the second place, the paper aims to offer a critique of the standard of compelling reasons employed in the Ibrahim Judgment. In order to achieve its aim, this paper primarily analyses the jurisprudence of the European Human Court of Human Rights in the cases of Salduz v. Turkey, Ibrahim and Others v. the United Kingdom, and Beuze v. Belgium. Besides, the paper also touches upon other judgments of the European Court of Human Rights related to its subject. The paper in question, therefore, primarily relies on the case-law method in achieving its aims. The paper concludes that in overturning the Salduz doctrine in relation to aspects examined in the paper, the European Court of Human Rights has exacerbated the legal standing of the person against whom criminal proceedings are being conducted.